Las víctimas en el sistema procesal penal reformado - Pásara Pazos, Luis (2015)
This article analyzes the negative impact of the reforms within the criminal systems in Latin America, both for those who suffer a crime, and those who are accused of having committed such crime. Supprted by empirical data, the author warns how the innovations of the reformed criminal proceedings (for example, the simplified court proceeding or the active role played by prosecutors), by enrolling into an authoritative legalculture, become in practice contrary to their likely design.